Penyelesaian Perselisihan Properti melalui Pendekatan Mediasi di Indonesia - Tantimin, Tantimin; Febriani, Emiliya; Putra, Dharma (Bhirawa Law Journal, 2024)
Land as a vital asset is one of the advantages of Indonesia, which is an agricultural country. The need for land has increased, leading to frequent land conflicts. The research method used in this research is normative research. Dispute issues can be resolved through litigation or non-litigation such as mediation. Mediation is an effective alternative in resolving disputes, with mediators helping to reach agreements without trial. However, there are obstacles such as temperament, low education level, and unclear land boundaries. Legal support for mediation is provided by law. It is important to understand the principles of mediation, which provides autonomy to the parties in achieving peace.